Methods for Accounting for Co-Teaching in Value-Added Models. Issue 1 (1st January 2017) - Hock, Heinrich; Isenberg, Eric
ABSTRACT: As states and districts incorporate value-added estimates into multiple-measures systems of teacher evaluation, it has become increasingly important to understand how to model value added when the same student is taught the same subject by multiple teachers. Roster data on teacher–student links that have been checked and confirmed by the teachers themselves show levels of co-teaching far beyond what appear in administrative data. Therefore, to help states and districts overcome a potential limitation in the use of value added, we propose and examine three methods estimating teacher value added when students are co-taught: the Partial Credit Method, Teacher Team Method, and Full Roster Method. The Partial Credit Method apportions responsibility between teachers according to the fraction of the year a student spent with each. This method, however, has practical problems limiting its usefulness. The Teacher Team Method and Full Roster Method presume that co-teachers share joint responsibility for the achievement of their shared students. We explore the properties of these methods and compare empirical estimates. Both methods produce similar estimates of teacher value added, but the Full Roster Method can be more easily implemented in practice.